Shelley’s “Ode to the west wind” as the Reflection and Expression of the Romantic Era - Christine Resnitriwati Respatio (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2019)
ABSTRACT Literary works usually as a mirror of the society is life. A literary work can represent historical, social and political background of an era. A poem as one of literary works can do the samething. In this paper, the writer took the Ode to the west wind by Shelley, that is as the Reflection of the Romantic Age. The writer used the History approach to understand the historical background of the Romantic Period, and the aspect of the Romanticism era to explore the contain of the poem. The result shows that Ode to The West Wind is really reveals the condition of that era. Key words: romanticism, imagination, individual, the post, nature.